Do individual auditors from more religious hometowns enhance audit quality?: evidence from an Islamic country - Ocak, Murat (Journal of business ethics, 2024)
This study investigates the effect of individual auditors from more religious hometowns on audit quality, utilizing social identity and social norm theories via a sample of Turkish companies listed on the Borsa Istanbul and their associated individual auditors between the years 2010 and 2019. The sample includes a unique hand-collected dataset and secondary data gathered from various sources. The main findings demonstrate that individual auditors from more religious hometowns provide higher quality audit work in terms of the magnitudes of discretionary accruals, audit reporting aggressiveness, and the presence of small profits. In order to overcome potential endogeneity and selection problems, this study employs the Heckman two-stage estimation procedure, instrumental variables, system generalized methods of moments regressions, and propensity score matching-difference and differences method. The results of these additional tests also support the main results. When controlled for the religiosity levels of the province where clients operate and the religiosity levels of the province where individual auditors attended and graduated from universities, the results remain similar. The employment of alternative audit firm size and quality proxies also provides additional supportive evidence. The findings are robust when alternative variables of interest and alternative audit quality measures, such as sanction and restatement, are employed in the main models.